Consistent Distribution of Irrigation Water on Vertical Gardens (With Water As Content Sample) - Daud, Arifin; Indriyati, Citra; Sari, Julia Indah (PT Mattawang Mediatama Solution, 2022)
As the population increases and infrastructure development continues to increase, the need for green open space is decreasing. A vertical garden is an efficient solution with a vertically modern garden concept that the functions of green open spaces can be fulfilled. The irrigation system in a vertical garden gives a major role because plants can be grown well if they have a great irrigation system. Drip irrigation is one type of irrigation system that is widely applied and the best method that has been used in the world because it is considered more efficient with a small discharge, can reduce runoff, and can reduce water loss due to evaporation. This study aims to analyze the uniform of water distribution in the drip irrigation system and the average variation of water distribution in the row and column direction using a statistical test with Kruskal-Wallis. Based on the statistical analysis, it is obtained the coefficient of variation (Cv) of 0.27, the uniformity statistic (Us) of 73.2%, and the coefficient of uniformity (Uc) of 71.7% which means that the three parameters are categorized as good and acceptable while for statistical tests Kruskal-Wallis has a difference in the average variation of water distribution for the row and column groups.